Perception of plantation student toward career in plantation / Mohamad Hafiz Sulaiman - Sulaiman, Mohamad Hafiz (Faculty of Plantation and Agrotechnology, 2017)
The plantation sector, especially the oil palm commodity, is currently the largest agricultural based contributor to Malaysia economic projection involving both upstream and downstream activities. The rapid expansion in this palm oil industry caused a necessary high labor momentum in this sector. In the side of management in plantation, many institutes provide the course that brings the student involved in that field and exposed them to the environment in plantation. That situation may be accept by certain student and may not be accepted by some of them. This study was done in order to analyses the pull or push factors in constructing a particular pattern of perception among the selected respondents. Accordingly, they were selected from their study in plantation field that have more exposed program to make them enter or not to plantation sector. A survey method through questionnaire was used to collect data from 188 of plantation student in UiTM respondents which were selected using random sampling method. Descriptive analysis was applied based on the factors of perceptions of plantation student to work in plantation. The factor that influences the perception and willingness of this group of student to choose plantation as one of the career has been determined in result and discussion section in this research paper.